Prevalence and correlates of neurocognitive impairment and psychiatric disorders among schoolchildren in Wakiso District, Uganda: a cross-sectional study - Nampijja, Margaret; Sembajjwe, Wilber; Mpairwe, Harriet; Mpango, Richard; Kinyanda, Eugene (Wellcome open research, 2021)
<ns3:p><ns3:bold>Background:</ns3:bold> There is limited data on the burden of mental disorders among ‘healthy’ children in Africa. We examined the prevalence and correlates of neurocognitive and psychiatric disorders among schoolchildren in Uganda.</ns3:p><ns3:p> <ns3:bold>Methods</ns3:bold>: This cross-sectional study enrolled 322 schoolchildren aged 5-17years in Wakiso, Uganda. We assessed for neurocognitive impairment using the Kaufmann-Assessment-Battery, and psychiatric disorders (major-depressive-disorder (MDD), attention-deficit-hyperactivity-disorder (ADHD), generalised-anxiety-disorder (GAD), and substance-use-disorder (SUD)) using the parent version of the Child and Adolescent Symptom Inventory-5, and Youth Inventory-4R Self Report. Prevalence and risk factors were determined using percentages and logistic regression.</ns3:p><ns3:p> <ns3:bold>Results:</ns3:bold> Twenty-five participants (8%) had neurocognitive impairment. Nineteen (5.9%) participants had MDD, nine (2.8%) had ADHD, seven (2.2%) had GAD, 14 (8.6%) had SUD; and 30 (9.3%) had any psychiatric disorder. None of the factors examined were associated with the disorders.</ns3:p><ns3:p> <ns3:bold>Conclusions:</ns3:bold> The unexpectedly high burden of mental disorders in this general population of children warrants targeted screening of those at risk, and treatment of those affected. Further, future studies should extensively investigate the factors that underlie the identified psychiatric disorders in this and similar general populations.</ns3:p>
Keywords: openalex:import